Should Compulsory Education Laws be Modified? - Antonita Diederich (Educational Considerations, 1973)
Laws requiring school attendance "should be modified to include funding and sanction for programs geared to meet individual needs and cultural differences," this teacher contends. The goal is to have students stay in school not because they have to, but because they want to.